2016
DOI: 10.1177/2050312115624333
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomically actionable medications in a safety net health care system

Abstract: Objective:Prior to implementing a trial to evaluate the economic costs and clinical outcomes of pharmacogenetic testing in a large safety net health care system, we determined the number of patients taking targeted medications and their clinical care encounter sites.Methods:Using 1-year electronic medical record data, we evaluated the number of patients who had started one or more of 30 known pharmacogenomically actionable medications and the number of care encounter sites the patients had visited.Results:Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…Many patients would be willing to undergo testing again in the future, and many indicated that they'd prefer to undergo preemptive testing to avoid any delays in treatment. It has been estimated that the use of preemptive PGx testing could be helpful in preventing a significant number of adverse events given the multiple commonly used medications with known PGx interactions that patients will likely be prescribed [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients would be willing to undergo testing again in the future, and many indicated that they'd prefer to undergo preemptive testing to avoid any delays in treatment. It has been estimated that the use of preemptive PGx testing could be helpful in preventing a significant number of adverse events given the multiple commonly used medications with known PGx interactions that patients will likely be prescribed [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…(2,4) For example, a recent retrospective analysis of EHR data in a safety-net health system found that 7,039 patients across a 73-site system initiated a prescription for at least one of 30 clinically actionable pharmacogenetic medications during the 12-month study period (the most common identified medications included tramadol, clopidogrel, and codeine). (20) As costs of panel-based genotyping become comparable to or even lower than single-gene assays because of the ability to batch samples from multiple patients to genotype together, it is logical that a preemptive model would become increasingly cost effective on a large scale, but definitive data supporting this assumption do not exist.…”
Section: Supporting Development Of Pragmatic Preemptive Pharmacogenementioning
confidence: 99%
“…To identify all the appellations, we combed through the list of all orderable medication names (43,300) in this EHR. In earlier preparatory work to estimate the volume of pharmacogenomics-relevant medication use, we also reviewed all dispensed medication names (417,000) [18]. In these ways we honed the normalization of the different strengths, routes, and combination forms.…”
Section: Using the Ehr To Identify Eligible Patientsmentioning
confidence: 99%